Investigation of the Elastic Properties of Graphenylene Using Molecular Dynamics Simulations - Rouhi,Saeed (2017)
Molecular dynamics simulations are used here to study the mechanical behavior of graphenylene under uni-directional and bi-directional loadings. The effects of nanosheet chirality and size on Young's modulus of graphenylene are investigated. Compared to graphene, graphenylene possess a smaller elastic modulus. It is shown that for large armchair and zigzag graphenylenes, the effect of nanosheet size on the mechanical properties can be neglected. It is observed that increasing temperature results in decreasing Young's modulus of graphenylene. Besides, fracture of graphenylene occurs at large strains. Moreover, it is represented that for small graphenylenes, bulk modulus is significantly sensitive to the size variation. However, this sensitivity disappears for large nanosheets.